2018
DOI: 10.3390/geosciences8060201
|View full text |Cite
|
Sign up to set email alerts
|

Global Warming Can Lead to Depletion of Oxygen by Disrupting Phytoplankton Photosynthesis: A Mathematical Modelling Approach

Abstract: Abstract:We consider the effect of global warming on the coupled plankton-oxygen dynamics in the ocean. The net oxygen production by phytoplankton is known to depend on the water temperature and hence can be disrupted by warming. We address this issue theoretically by considering a mathematical model of the plankton-oxygen system. The model is generic and can account for a variety of biological factors. We first show that sustainable oxygen production by phytoplankton is only possible if the net production rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Similarly, the density has been positively in uenced by depth during winter, higher depths were observed in the river as similar to the Gharraf river of Iraq (Al-Husseini et al, 2020). A signi cant positive correlation with Dissolved oxygen was also observed, during the daytime with sunlight, the photosynthetic activities of the phytoplankton get enhanced, and relatively more oxygen is released in the aquatic system when the numbers of Phytoplankton are higher and is also depending on water temperature (Sekerci et al, 2018). The higher dissolved oxygen in the riverine system has also been reported during the post-monsoon and winter season.…”
Section: 3physico-chemical Propertiesmentioning
confidence: 69%
“…Similarly, the density has been positively in uenced by depth during winter, higher depths were observed in the river as similar to the Gharraf river of Iraq (Al-Husseini et al, 2020). A signi cant positive correlation with Dissolved oxygen was also observed, during the daytime with sunlight, the photosynthetic activities of the phytoplankton get enhanced, and relatively more oxygen is released in the aquatic system when the numbers of Phytoplankton are higher and is also depending on water temperature (Sekerci et al, 2018). The higher dissolved oxygen in the riverine system has also been reported during the post-monsoon and winter season.…”
Section: 3physico-chemical Propertiesmentioning
confidence: 69%
“…The decrease was previously linked to purely physical mechanisms such as the decrease of oxygen solvability in warmer waters [23,24]. More recently, however, it was shown that global warming can significantly affect the amount of dissolved oxygen also through a biological mechanism as it can disrupt the oxygen production by phytoplankton potentially leading to global ocean anoxia [10,12,25]. Moreover, since it is estimated that about 70% of the atmospheric oxygen is produced in the ocean, such a global disruption of oxygen production would eventually lead to a significant decrease of the oxygen concentration in the air and could hence lead to mass mortality of animals and humans.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…This is responsible for around 60% of our oxygen, but warming seas are destroying it. If present trends continue it is predicted that oxygen depletion will mean that we will all effectively be living in the kind of atmosphere we associate with the summit of Everest (Sekerci and Petrovskii 2018).…”
Section: The Four Horsemenmentioning
confidence: 99%